IMPLEMENTATION OF TAHSIN AND TAHFIDZ LEARNING MODELS TO IMPROVE STUDENTS' MEMORY ABILITY IN SD ISLAM AMANAH UMMAH SURAKARTA - Sugiyanto, S; Khoir, Mulyanto Abdullah (Proceeding of International Conference of Islamic Education, 2023)
This study aims to investigate the application of the Tahsin and Tahfidz learning models as an effective method for improving students' memorization skills at SD Islam Amanah Ummah Surakarta. Memorizing ability is an important aspect of Islamic religious education, which involves memorizing verses of the Qur'an and prayers. The research method used was classroom action research involving students at SD Islam Amanah Ummah Surakarta as research subjects. The application of the Tahsin and Tahfidz learning models is carried out in several stages which include planning, implementation, observation, and reflection. In addition, research instruments in the form of rote tests and participatory observations were used to collect data about students' memorization abilities before and after the application of the learning model. The results showed that there was a significant increase in students' memorization ability after applying the Tahsin and Tahfidz learning models. This can be seen from the increase in the average score of students' memorization tests and their active participation during the learning process. Students also showed a more positive inclination towards learning the Islamic religion and a passion for continuing to improve their memorization skills. In conclusion, the application of the Tahsin and Tahfidz learning models is effective in improving students' memorization skills at SD Islam Amanah Ummah Surakarta. This model can be used as a useful alternative in the context of Islamic religious education in other schools. It is suggested that further research be conducted to broaden the scope of this research and measure the long-term impact of implementing this learning model on students' memorization abilities.